The Effect Ecological Citizenship on Critical Thinking Skills of Elementary School Student - Anshory, Meilana Umi; Triyanto, Triyanto; Tarsidi, Deni Zein (Universitas Sebelas Maret, 2025)
Amidst of global environmental challenges, ecological awareness as a form of ecological citizenship is believed to have an influence on the critical thinking skills of elementary school students. This study aims to analyze the influence of ecological citizenship on the critical thinking skills of elementary school student through a systematic literature review of selected scientific articles. The method used is a meta-synthesis of literature,which includes the stages of identification, selection, and thematic analysis based on a systematic protocol. The results of the study indicate that ecological citizenship has a significant relationship with critical thinking skills: international studies found a positive correlation, while national studies showed an increase in analytical thinking after environmental citizenship program interventions. A deep ecological understanding encourages students to evaluate information based on evidence, consider environmental ethical implications, and make reflective decisions. Furthermore, the integration of ecological education into leraning has been proven to strengthen critical thinking habits systenatically. Conclusion, ecological citizenship significantly contributes to the development of critical thinking in elementary school students and need to be strategically integrated into the elementary school curriculum.